VARIASI QIRA’AT DAN LATAR BELAKANG PERBEDAAN QIRA’AT - Aida Aida; Aisya Nur Faradila; Annisa Kartika Dewi (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2022)
Qira'at is a way of reading the Qur'an in accordance with the teachings of the Prophet in a tauqify manner. while the science of Qira'at is the study of various methods (ways) of reading the Qur'an. Qira'at grouping with six reading versions, namely: Mutawatir, Masyhur, Ahad, Syadz, Maudlu ', Mudraj. Studying the science of qira'at can provide benefits and understanding for those who study it, including: being able to strengthen the legal provisions that have been agreed upon by the scholars, being able to judge the law that is disputed by the scholars, being able to combine two different provisions, being able to show two different legal provisions. different in 11 different conditions, and can provide an explanation of a word in the Qur'an that may be difficult to understand its meaning